Assessing the effectiveness of Byssochlamys nivea and Scopulariopsis brumptii in pentachlorophenol removal and biological control of two Phytophthora species. Issue 4 (April 2016) - Bosso, Luciano; Scelza, Rosalia; Varlese, Rosaria; Meca, Giuseppe; Testa, Antonino; Rao, Maria A.; Cristinzio, Gennaro
Abstract: Bioremediation and biological-control by fungi have made tremendous strides in numerous biotechnology applications. The aim of this study was to test Byssochlamys nivea and Scopulariopsis brumptii in sensitivity and degradation to pentachlorophenol (PCP) and in biological-control of Phytophthora cinnamomi and Phytophthora cambivora. B. nivea and S. brumptii were tested in PCP sensitivity and degradation in microbiological media while the experiments of biological-control were carried out in microbiological media and soil. The fungal strains showed low PCP sensitivity at 12.5 and 25 mg PCP L −1 although the hyphal size, fungal mat, patulin, and spore production decreased with increasing PCP concentrations. B. nivea and S. brumptii depleted completely 12.5 and 25 mg PCP L −1 in liquid culture after 28 d of incubation at 28 °C. Electrolyte leakage assays showed that both fungi have low sensitivity to 25 mg PCP L −1 and produced no toxic compounds for the plant. B. nivea and S. brumptii were able to inhibit the growth of the two plant pathogens in laboratory studies and reduce the mortality of chestnut plants caused by two Phytophthorae in greenhouse experiments. The two fungal strains did not produce volatile organic compounds able to reduce the growth of two plant pathogens tested.